Overview of Elderly Knowledge About Self-Care at the Kayon Public Health Center in Palangka Raya City - Siska, Helni Dea; Sari, Anggita; Putri, Dian Purnama (Global Writing Academica Researching & Publishing, 2025)
Self-care is an activity carried out by a person to maintain their health independently. It aims to maintain health and encourage the development and prevention of disease. This study aims to determine the description of elderly knowledge about self-care at the Kayon Community Health Center in Palangka Raya City. This study uses a descriptive research type with an elderly population in the Kayon Community Health Center work area and the research sample uses a purposive sampling technique with a sample size of 55 elderly. The study shows that respondents based on age are mostly aged 60-69 years with a total of 54 respondents (98.18%), based on gender, they are dominated by men with a total of 30 respondents (54.55%), based on marital status, the majority are married with a total of 49 respondents (89.09%) and education is mostly in the tertiary category with a total of 31 respondents (56.36%). Based on knowledge, the majority of respondents had good knowledge of self-care (30 respondents (54.55%), respondents had sufficient knowledge (22 respondents (40%), and respondents had insufficient knowledge (3 respondents (5.55%). Overall, the elderly in this study had a good level of knowledge regarding self-care, which reflects an adequate understanding of how to maintain health in old age. However, efforts are still needed to improve health education for elderly with sufficient and insufficient levels of knowledge to achieve an optimal quality of life.